2017
DOI: 10.3892/mmr.2017.7123
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNA-mRNA crosstalk in laryngeal squamous cell carcinoma

Abstract: The aim of the present study was to elaborate the underlying pathogenesis of laryngeal squamous cell carcinoma (LSCC). Micro (mi) RNA and messenger (m) RNA expression profiling of patients with LSCC were downloaded from The Cancer Genome Atlas (TCGA) database. Differentially expressed miRNAs (DEMIs) and differentially expressed mRNAs (DEMs) were identified in LSCC compared to normal control tissues. The DEMs targeted by DEMIs were identified and the negative correlation between DEMs and DEMIs was subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Initiation and progression of cancer are often caused by an imbalance between oncogenes and tumor suppressive genes. From The Cancer Genome Atlas (TCGA) database, a number of differentially expressed miRNAs in LSCC have been identified [11]. Several miRNAs, including miR-26a and miR-153, emerged as powerful regulators in LSCC, as indicated in recent studies [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Initiation and progression of cancer are often caused by an imbalance between oncogenes and tumor suppressive genes. From The Cancer Genome Atlas (TCGA) database, a number of differentially expressed miRNAs in LSCC have been identified [11]. Several miRNAs, including miR-26a and miR-153, emerged as powerful regulators in LSCC, as indicated in recent studies [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…9 d). ECM-receptor interaction was considered as potential role in participating in multiple tumor biology such as motility, invasion, and metastasis process of LSCC [ 32 ]. Researchers found that silencing of the WNT-5A receptors Frizzled 8 (FZD8) and RYK attenuated TGF-β-induced ECM expression [ 33 ]; future work needs to be done to analyze the expression status of RYK in different tumor stages and its role in progression of LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, miRNAs influence the occurrence, development and metastasis of LSCC through complex mechanisms, and thus the discovery of new miRNAs in LSCC tissues is very important for the diagnosis and treatment of LSCC ( Liu & Ye, 2019 ). The purposes of this study were to screen for differentially expressed miRNAs and mRNAs in LSCC using molecular biology and bioinformatics techniques, to successfully predict miRNA target genes, and to construct a miRNA-mRNA regulatory network based on the relationships between miRNAs, mRNA, of miRNA target genes and differential expression ( Guan et al, 2015 ; Fei et al, 2017 ; Ma et al, 2021 ). Next, further evaluation was performed using gene ontology (GO) and Kyoto Encyclopedia for gene and genome (KEGG) path analysis.…”
Section: Introductionmentioning
confidence: 99%